2012
DOI: 10.1186/1476-072x-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Geographical epidemiology of antibacterials in the preschool age

Abstract: BackgroundThematic maps allow a more rapid and immediate reading of the geographical differences in the distribution of data referred to a specific territory. The aim of this study was to show, for the first time, the application of some statistical and cartographic tools in the analysis of drug utilization in the pediatric population of an Italian region, and to assess the intra-regional difference in the antibiotic prescriptions.MethodsTo assess the type of geographic distribution of the prescriptions, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…A 1998 study on paediatric prescriptions in southern Italy showed similar results concerning drug classes, with a higher average number of active substances prescribed by family paediatricians . The prevalence rate of antibiotic drugs observed was high compared to that of most of the other European countries, but is similar to reports in the literature concerning Italian children .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A 1998 study on paediatric prescriptions in southern Italy showed similar results concerning drug classes, with a higher average number of active substances prescribed by family paediatricians . The prevalence rate of antibiotic drugs observed was high compared to that of most of the other European countries, but is similar to reports in the literature concerning Italian children .…”
Section: Discussionsupporting
confidence: 87%
“…Children are one of the patient populations most exposed to drugs . Wide qualitative and quantitative differences have been documented in the international literature, and within countries and regions, that are most likely not due to differences in the epidemiology of diseases . A wide range of drugs is prescribed for Italian paediatric patients, but there are only a limited number of active substances that are commonly prescribed by the majority of paediatricians .…”
Section: Introductionmentioning
confidence: 99%
“…We already documented that in the areas where antibiotic prevalence is higher, high prescribing paediatricians are more frequent. 7 In this regard, the current study adds relevant findings concerning quality of prescriptions.…”
Section: Discussionmentioning
confidence: 85%
“…The paediatrician’s prescribing attitude has already been identified as one of the main determinants of differences in antibiotic prevalence at the area level. 7 Despite this, the association between the amount of antibiotics prescribed and the qualitative profile is a scantly studied topic. Moreover, most epidemiological studies on drug prescription patterns are based on administrative databases that rarely contain the indication for the prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Friedman's nonparametric ANOVA was used to test inter-year differences in malaria incidence in MSY. The odds ratio with a 95% CI was used.Analysis of spatial clustering in clinical malaria was performed by using hot spot analysis Getis-Ord'sGi*(d) statistics (Cartabia et al, 2012; Dhimal et al, 2014; Haque et al, 2014; Haque et al, 2012; Kelly-Hope et al, 2009; Ruktanonchai et al, 2014; Saxena et al, 2012). Statistical analysis and spatial clustering were conducted using STATISTICA 10.0 (StatSoft Inc., Tulsa, OK, USA) and ArcGIS 10.3 for Desktop (ESRI, Redlands, CA, USA), respectively.…”
Section: Methodsmentioning
confidence: 99%